PENGARUH QUANTUM TEACHING TERHADAP PEROLEHAN BELAJAR IPS PESERTA DIDIK DI SEKOLAH DASAR NEGERI PONTIANAK - Thoyibah, Thoyibah; Marzuki, Marzuki; Sugiyono, Sugiyono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research purpose was to know the influence of applying Quantum Teaching approach to social study result of fifth grade students of Sekolah Dasar Negeri 09 Pontianak Timur. The research method was experimental as Pre-Experimental Design of non equivalent control group design. The population of all students from three classes is 94 people, the sample of this research is VB students with 31 people as experimental classes and VC as a control class with 31 people. The used data collection techniques were measurement techniques and data collector tools are written tests of multiple choice. The average post-test results of experimental class is 77.63 and the control post-test average is 73.89. The result of hypothesis test using t-test (T-test) obtained t = 1.864 where as for dk (31+31-2 = 60) with significance level α = 5% obtained t count table= 1,676, which means t count > t table , this proves that there is an effect of applying Quantum Teaching approach in social study. Based on result of calculation of effect size (ES) obtained ES = 0.35 which included medium criteria. This it can be said that the applying Quantum Teaching approach positive influence to social study result of fifth grade students of Sekolah Dasar Negeri 09 Pontianak Timur. Keywords: Influence, Quantum Teaching, Social Studies.